Catestatin: Antimicrobial Functions and Potential Therapeutics - Suborno Jati; Sumana Mahata; Soumita Das; Saurabh Chatterjee; Sushil K. Mahata (MDPI AG, 2023)
The rapid increase in drug-resistant and multidrug-resistant infections poses a serious challenge to antimicrobial therapies, and has created a global health crisis. Since antimicrobial peptides (AMPs) have escaped bacterial resistance throughout evolution, AMPs are a category of potential alternatives for antibiotic-resistant "superbugs". The Chromogranin A (CgA)-derived peptide Catestatin (CST: hCgA352-372; bCgA344-364) was initially identified in 1997 as an acute nicotinic-cholinergic antagonist. Subsequently, CST was established as a pleiotropic hormone. In 2005, it was reported that N-terminal 15 amino acids of bovine CST (bCST1-15 aka cateslytin) exert antibacterial, antifungal, and antiyeast effects without showing any hemolytic effects. In 2017, D-bCST1-15 (where L-amino acids were changed to D-amino acids) was shown to exert very effective antimicrobial effects against various bacterial strains. Beyond antimicrobial effects, D-bCST1-15 potentiated (additive/synergistic) antibacterial effects of cefotaxime, amoxicillin, and methicillin. Furthermore, D-bCST1-15 neither triggered bacterial resistance nor elicited cytokine release. The present review will highlight the antimicrobial effects of CST, bCST1-15 (aka cateslytin), D-bCST1-15, and human variants of CST (Gly364Ser-CST and Pro370Leu-CST); evolutionary conservation of CST in mammals; and their potential as a therapy for antibiotic-resistant "superbugs".